SCIENCE AND TECHNOLOGY IN THE QUR'AN ( STUDY OF ISLAMIC EDUCATIONAL PHILOSOPHY) - Shynta Sri Wahyuni Ginting; Ahmad Syukri; Salminawati Salminawati (Reflektika, 2023)
This observation aims to carry out studies on aspects related to science and technology based on the perspective of the Koran, including positive and negative impacts on life. Researchers used a qualitative descriptive approach using library research (library research). Researchers carried out data collection techniques with information analysis techniques using inductive and deductive analysis and documentation. The study results obtained data if science and technology are based on the point of view of the pure Qur'an because they are still needed in human activities; therefore, they must be upheld and provide a lot of relief for living things. However, in practice, it should be considered more carefully. This is also related to the positive and negative impacts that arise, so appropriate wisdom is needed so as not to cause harm to others in living life.